2019
DOI: 10.3390/healthcare7040162
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of Dietary Antioxidants against Cervical Cancer versus the Promotive Effect of Tobacco Smoking

Abstract: Uterine cervical cancer is the fourth most common cancer in women, and its etiology has been recognized. High-risk human papilloma virus (HR-HPV) infection induces an opportunity for malignant transformation. This paper discusses the current issues based on a review of the literature and compares the impact of the dietary and nutrient intake to the impact of tobacco smoking on cervical cancer development. The important roles of diet/nutrition in cervical cancer are as prophylaxis against HR-HPV infection. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the etiology of the formation of squamous intraepithelial lesions (SIL), HPV infection leads to the release of different inflammation mediators, resulting in the formation of reactive oxygen species (ROS) and causing a decrease in the level of antioxidants. HPV integration in combination with oxidative stress causes oxidative damage to the genome and different epigenetic alterations that altogether hinder apoptosis and alter cellular proliferation [ 3 ]. Therefore, diet components exerting antiviral, anti-inflammatory and antioxidant actions could be considered protective against the progression of SIL and the development of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the etiology of the formation of squamous intraepithelial lesions (SIL), HPV infection leads to the release of different inflammation mediators, resulting in the formation of reactive oxygen species (ROS) and causing a decrease in the level of antioxidants. HPV integration in combination with oxidative stress causes oxidative damage to the genome and different epigenetic alterations that altogether hinder apoptosis and alter cellular proliferation [ 3 ]. Therefore, diet components exerting antiviral, anti-inflammatory and antioxidant actions could be considered protective against the progression of SIL and the development of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies confirm that Western dietary patterns increase the possibility of HPV infection, while high adherence to the Mediterranean diet decreases the risk [ 4 ]. Numerous observational studies indicate that the consumption of a wide variety of whole foods rich in vitamins, minerals and nonessential bioactive compounds (especially those with antioxidant and antiviral properties) can be effective in preventing the progression of LSILs to HSIL or cervical cancer, and, therefore, a balanced-diet prevention strategy should be recommended to patients upon LSIL diagnosis [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerators, in contrast, include environmental, immunological, and lifestyle cofactors such as cigarette smoking, diet, oral contraceptive (OC) use, parity, and coinfection with other sexually transmitted infections [ 10 ]. Indeed, we previously reviewed the effect of cigarette smoking on the risk of cervical cancer development [ 71 , 72 ], hypothesizing that the promotive effect of smoking may be stronger than the preventive effect of antioxidant intake against cervical cancer. Wei et al suggested that in HR-HPV-infected cells, tobacco smoking not only causes DNA adducts and strand breaks [ 73 ], but also causes an increase in the viral load [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been shown to be an independent risk factor for HSIL in young women after the onset of frequent sexual activity (Collins et al, 2010). Several studies have shown (International Collaboration of Epidemiological Studies of Cervical Cancer et al, 2006;Koshiyama et al, 2019) that smokers have an increased risk of developing cervical cancer compared with nonsmokers, and that the risk of squamous cell carcinoma of smokers increases with the number of cigarettes smoked every day and with decreasing age of smoking initiation. Inamine et al (2012) found that smoking induces high plasma expression of vascular endothelial growth factor C (VEGF-C) in patients with CIN and that VEGF-C plays a major role in cervical lesions in smoking patients.…”
Section: Maternity and Smokingmentioning
confidence: 99%